Girardia festae (Borelli, 1898) (Platyhelminthes: Tricladida: Dugesiidae): Distribution extension in a high-altitude lake from Colombia - Brusa, Francisco (2012)
We revise the Neotropical distribution of Girardia festae (Platyhelminthes, Dugesiidae) following a new record in a Colombian high-altitude lake. G. festae is a freshwater planarian known mainly in the Andean Cordillera from Venezuela to Argentina. The species' key reproductive features include: ventral testes, bottle-like penis papilla, and sperm ducts joining to the penis bulb latero-dorsally.